BEAUTY MYTH AND ITS EFFECTS SEEN IN THE MISS CONGENIALITY (2000) MOVIE - Dita Ulfiani; Riana Permatasari (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
This study examines the beauty myths depicted by female characters in the film Miss Congeniality (2000), including Gracie, Cheryl, Leslie, and Mary. The film follows Gracie, a female FBI agent who goes undercover as a beauty pageant entrant, forcing her and the other participants to conform to society's beauty standards through the use of beauty myths. The purpose of this study is to establish which areas are affected by the beauty myth and how it affects the main character. This study employed a qualitative methodology. This study used Naomi Wolf’s theory of beauty myth. The scripts for Miss Congeniality (2000) served as the primary data for this study. Secondary data for this study included books, articles, journals, and e-books. The data-gathering processes included watching the movie, reading the movie script, identifying the data, classifying the data, and reducing the data. The study yielded two findings. First, the beauty myth affected four of the six areas examined: culture, hunger, violence, and sex. Second, the beauty myth caused two effects: unsatisfied and suffer. Gracie feels unsatisfied and suffer with her physical appearance as a result of this.